The Application of the ThroLy Risk Assessment Model to Predict Venous Thromboembolism in Patients with Diffuse Large B-Cell Lymphoma. (September 2021) - Abdel-Razeq, Hikmat; Ma'koseh, Mohammad; Mansour, Asem; Bater, Rayan; Amarin, Rula; Abufara, Alaa; Halahleh, Khalid; Manassra, Mohammad; Alrwashdeh, Mohammad; Almomani, Mohammad; Zmaily, Mais
Background: Patients with aggressive lymphomas are at higher risk for venous thromboembolism (VTE). ThroLy is a risk assessment model (RAM) derived to predict the occurrence of VTE in various types of lymphomas. In this study, we assess the clinical application of ThroLy RAM in a unified group of patients with diffuse large B-cell lymphoma (DLBCL). Methods: Hospital databases were searched for patients with DLBCL and radiologically-confirmed VTE. Items in the ThroLy RAM, including prior VTE, reduced mobility, obesity, extranodal disease, mediastinal involvement, neutropenia and hemoglobin < 10.0 g/dL, were retrospectively reviewed. Results: A total of 524 patients, median age 49 (range: 18-90) years were included. Patients had high disease burden; 57.3% with stage III/IV and 34.0% with bulky disease. All were treated on unified guidelines; 63 (12.0%) had primary refractory disease. Venous thromboembolic events were reported in 71 (13.5%) patients. Among 121 patients with high (> 3) ThroLy score, 22.3% developed VTE compared to 8.4% and 12.4% in those with low and intermediate risk scores, respectively ( P = .014). Simplifying the ThroLy model into two risk groups; high-risk (score ≥ 3) and low risk (score < 3) can still segregate patients; VTE developed in 44 (17.2%) high-risk patients ( n = 256) compared to 27 (10.1%) in the low-risk group ( n = 268), P = .038. Neutropenia, a component of the ThroLy, was encountered in only 14 (2.7%) patients. Conclusions: ThroLy RAM can identify patients with DLBCL at high risk for VTE. Model can be modified by dividing patients into two, rather than three risk groups, and further simplified by omitting neutropenia.